Frequency of Immune-Histochemical Markers-Based Diffuse Large B Cell Lymphoma Subgroups (Medical Forum Monthly, 2023)
Objective: To assess the frequency of diffuse large B cell lymphoma subgroups by immune-histochemical markers.Study Design: A Descriptive Cross-Sectional StudyPlace and Duration of Study: This study was conducted at the Department of Histopathology. Rehman College of Dentistry / Rehman Medical Institute (RCD/RMI), Peshawar from August 2022 to February 2023.Methods: DLBCL was diagnosed using a“panel of lymphoid antibodies that comprised CD20, CD79a, CD3, Ki-67, and Pax5”. On silane-coated slides, slices were mounted for immunohistochemical staining. To analyze the data, IBM SPSS version 23 was used. Results: In the current study, 80 patients were enrolled. The male patients were 45 (56.25%), and females were 35 (43.75%). Our study's mean age (SD) was 42 (4.43) years. Of 80 cases, 37 (46.25%) cases were observed as a germinal centres, while 43 (53.75%) were observed as non-germinal centre-like subgroups. In our study, 45 (56.25%) cases were observed as extranodal while 35(43.75%) cases were observed as nodal lymphoma.Conclusion: Our study concludes that the frequency of the non-germinal sub-group of diffuse large B-cell lymphoma is higher than the germinal centre-like sub-group.